Ecological divergence of burying beetles into the forest canopy - Jillian D. Wettlaufer (PeerJ, 2018)
Closely related species with overlapping geographic ranges encounter a significant challenge: they share many ecological traits and preferences but must partition resources to coexist. In Ontario, potentially eleven species of carrion beetles (Coleoptera: Silphidae) live together and require vertebrate carrion for reproduction. Their reliance on an ephemeral and uncommon resource that is unpredictable in space and time is thought to create intense intra- and interspecific competition. Evidence suggests that burying beetle species reduce competition by partitioning carrion for breeding across different habitats, temperatures, and seasons. Here, we test predictions of an alternative axis for partitioning carrion: vertical partitioning between the ground and forest canopy. We conducted a survey of carrion beetles from May to July 2016 at the Queen’s University Biological Station across 50 randomly generated points using baited lethal traps at zero and six metres. Ground traps yielded more species and individuals compared to those in the canopy, and the number of individuals and species caught increased through the season in both trap types. Ground and canopy traps were accurately distinguished by the presence or absence of three species: ground traps contained more Nicrophorus orbicollis and Necrophila americana, while canopy traps contained more Nicrophorus pustulatus. We trapped 253 N. pustulatus in the canopy, but only 60 on the ground. N. pustulatus is thought to be rare across its geographic range, but our results suggest it is uniquely common in canopy habitats, demonstrating a vertical partitioning of habitat and resources. Our results are consistent with N. pustulatus having diverged into canopy habitats as a strategy to coexist with closely related sympatric species when competing for similar resources. We still, however, do not know the traits that allow N. pustulatus to flourish in the canopy, exactly how N. pustulatus uses canopy resources for breeding, or the factors that restrict the expansion of other burying beetles into this habitat.